A Mobile-Based Fiction and Non-Fiction Book Vertical Marketing System - Syahfriani Syahfriani; Boni Oktaviana Sembiring; Edrian Hadinata (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2022)
It is simpler for vendors to advertise and market their goods to a larger audience online. Due to how simple it is to get information online, sales of fiction and non- fiction books are one of the industries that have begun to decline. Therefore, an online sales system is required to assist both purchasers and sellers of books, notably fiction and non-fiction books. It will be possible for resellers to market their books with the aid of this method for selling fiction and non-fiction books. The SDLC approach and the business process system employ UML as their tools to develop or construct a book selling system. The system created for this study is web- and mobile-based, including web-based administrators and a mobile system for resellers and clients. As a consequence of this study, a system that can handle all online book sales procedures for both fiction and nonfiction books has been developed.